2011
DOI: 10.1038/bjc.2011.206
|View full text |Cite
|
Sign up to set email alerts
|

A genotype-directed phase I–IV dose-finding study of irinotecan in combination with fluorouracil/leucovorin as first-line treatment in advanced colorectal cancer

Abstract: Background:Infusional fluorouracil/leucovorin (FU/LV) plus irinotecan (FOLFIRI) is one of the standard first-line options for patients with metastatic colorectal cancer (mCRC). Irinotecan is converted into 7-ethyl-10-hydroxycamptothecin (SN-38) by a carboxylsterase and metabolised through uridine diphosphate glucuronosyl transferase (UGT1A1). The UGT1A1*28 allele has been associated with the risk of developing severe toxicities. The present trial was designed to define the maximum tolerated dose according to U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 23 publications
5
97
0
Order By: Relevance
“…However, the patient populations are quite different between our study (heavily pretreated, different tumor types) and the FOLFIRI studies (first-line treatment of metastatic colorectal cancer). 19,22 Similar to this study, these studies with FOLFIRI also showed that the patients with the *1/*28 genotype tolerated a lower dose relative to the patients with the *1/*1 genotype, confirming the importance of individualized dosing by genotype. The *1/*28 genotype confers an intermediatemetabolizer phenotype 13,[23][24][25] and an intermediate risk of toxicity.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, the patient populations are quite different between our study (heavily pretreated, different tumor types) and the FOLFIRI studies (first-line treatment of metastatic colorectal cancer). 19,22 Similar to this study, these studies with FOLFIRI also showed that the patients with the *1/*28 genotype tolerated a lower dose relative to the patients with the *1/*1 genotype, confirming the importance of individualized dosing by genotype. The *1/*28 genotype confers an intermediatemetabolizer phenotype 13,[23][24][25] and an intermediate risk of toxicity.…”
Section: Discussionsupporting
confidence: 68%
“…An irinotecan dose of 500 mg/m 2 has been shown to be tolerable in patients with refractory cancer who have favorable characteristics (eg, good risk, not heavily pretreated), 21 but UGT1A1*28 was not used for dose selection in that study. In other UGT1A1*28 genotypedirected studies of FOLFIRI, patients with the *1/*1 genotype tolerated approximately twice the dose recommended by the label, 19,22 probably because the therapeutic window is wider in the biweekly regimen of FOLFIRI (standard dose, 180 mg/m 2 ) than in the regimen administered once every 3 weeks (standard dose, 350 mg/m 2 ). However, the patient populations are quite different between our study (heavily pretreated, different tumor types) and the FOLFIRI studies (first-line treatment of metastatic colorectal cancer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, the US Food and Drug Administration recommended testing for UGT1A1 * 28 polymorphism for dose regulation of irinotecan. As regards colorectal cancer, studies on the optimal dose of irinotecan for the treatment of patients with low enzyme activity have been conducted (19,20). However, the optimal dose of irinotecan for lung cancer patients with low enzyme activity has not been determined and remains a subject of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this dose is insufficient in patients with the UGT1A1*1 allele and contributes to a poorer clinical outcome [7][8][9][10]. Conversely, 180 mg/m 2 of irinotecan in patients with homozygous UGT1A1*28 is associated with a greater number of severe adverse events (AEs) [7,11].…”
Section: Introductionmentioning
confidence: 99%